2020
DOI: 10.47536/jcrm.vi.301
|View full text |Cite
|
Sign up to set email alerts
|

Abundance estimates and trends for humpback whales (Megaptera novaeangliae) in Antarctic Areas IV and V based on JARPA sightings data

Abstract: Sighting survey data from the Japanese Whale Research Program under Special Permit in the Antarctic (JARPA) are analysed to obtain abundanceestimates for humpback whales (Megaptera novaeangliae) south of 60°S. The surveys were conducted during the 1989/90–2004/05 austral summerseasons (mainly in January and February); the survey areas alternated between Area IV (70°E–130°E) and Area V (130°E to 170°W) each year.Primary sighting effort totalled 293,811 n.miles over 6,188 days. Abundance estimates are obtained u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 3 publications
0
31
2
Order By: Relevance
“…Regarding other krill feeders, sighting surveys have shown that the abundance of large baleen whales increased substantially during the JARPA period e.g. blue (B. musculus) and southern right (Eubalaena australis) whales and especially humpback whales (Megaptera novaeangliae) (Branch et al, 2004;Branch and Rademeyer, 2003;Matsuoka et al, 2011). Thus it is possible that our results reflect the reverse of Laws' 'krill surplus hypothesis' (Laws, 1977).…”
Section: Groupsmentioning
confidence: 71%
“…Regarding other krill feeders, sighting surveys have shown that the abundance of large baleen whales increased substantially during the JARPA period e.g. blue (B. musculus) and southern right (Eubalaena australis) whales and especially humpback whales (Megaptera novaeangliae) (Branch et al, 2004;Branch and Rademeyer, 2003;Matsuoka et al, 2011). Thus it is possible that our results reflect the reverse of Laws' 'krill surplus hypothesis' (Laws, 1977).…”
Section: Groupsmentioning
confidence: 71%
“…Because stratum areas vary from year to year as a result of different ice edge locations, it is not immediately obvious whether such modeling approaches should be based on the density or on the abundance in a stratum, and arguments can be offered to support either approach. Matsuoka et al (2011) found little difference in results for the two approaches for humpback whales. This is also the case for the Antarctic minke whale abundances and their trends as indicated in Table 13 of this paper.…”
Section: Log-linear Modelsmentioning
confidence: 76%
“…This weakens the power of these data to detect such effects. For humpback whales, similarly no significant effect of survey mode and survey timing was detected (Matsuoka et al, 2011). Table 5 shows abundance trend estimates for equation ( 7)-( 10) in base case.…”
Section: Table 5fmentioning
confidence: 85%
See 1 more Smart Citation
“…These animals spend November to May in Antarctica feeding on Antarctic krill (Euphausia superba) and taking advantage of the highly productive upwellings (Jenner et al, 2001;Bestley et al, 2019). Historic whaling records and satellite tags show that this population resides in the Antarctic International Whaling Commission (IWC) Management Area IV during this time (Jenner et al, 2001;Matsuoka et al, 2011;Bestley et al, 2019). Amongst others, the Southern Kerguelen Plateau is a hotspot for phytoplankton blooms, which consequently attracts high densities of humpback whales during the feeding season (Schallenberg et al, 2018;Bestley et al, 2019).…”
Section: Introductionmentioning
confidence: 99%